European Monetary Union and foreign direct investment inflows - Pantelis Pantelidis; Dimitrios Kyrkilis; Efthymios Nikolopoulos (SPOUDAI - Journal of Economics and Business, 2012)
The aim of this paper is to construct and test a model explaining the inward Foreign Direct Investment (FDI) position of various members of European Monetary Union (EMU), on the basis of their location advantages during 1980-2010 period. The model focuses on the impact of EMU on FDI inflows and indicates that the monetary union has differentiated impact on FDI inflows across individual member countries. Euro zone membership is statistically significant but a negative determinant in the cases of Greece, Portugal, France, Belgium and Spain. Furthermore, for both Germany and Ireland the Euro area membership is a negative but statistically insignificant FDI inflow factor, while in the cases of Netherlands and Finland it is positive but also statistically insignificant. The results imply that countries with low competitiveness have not gained from the entrance in European Monetary Union, in terms of Foreign Direct Investment inflows.
Keywords: F10; F30; O50; 330; FDI; EMU; euro